Ny forståelse af velfærdsprofessionelle? - Jørgensen, Henning (Tidsskrift for Professionsstudier, 2025)
Occupational professionals in the public sector have been exposed to more kinds of pressure during more decades. New Public Management, especially, has orchestrated these. Welfare and administrative developments have weakened the power basis of these professionals - on all levels. More differentiations and hybridizations are to be recorded too. The article points to a new ecology for welfare professionals, changed demands and expectations as to behavior – including cross-professional work – and to changes in identities and identifications. Following this, a revision of the analytical understanding of occupational professionals is called for. Concepts from theories of the 20th century are no longer adequate in relation to the situation of today with external regulation. New theoretical positions are highlighted, and elements of a “connective professionalism” are discussed as professionalization this way might give expertise, responsibility and authority a renewal.